2020
DOI: 10.1186/s12957-020-1792-4
|View full text |Cite
|
Sign up to set email alerts
|

Smokers or non-smokers: who benefits more from immune checkpoint inhibitors in treatment of malignancies? An up-to-date meta-analysis

Abstract: Background: Immune checkpoint inhibitors, which are a milestone in anti-cancer therapy, have been applied in the treatment of multiple malignancies. Real-world data have suggested that smoking status may be associated with the efficacy of anti-PD-1/PD-L1 therapy. Hereby, to evaluate "smoking benefit or not", we included numerous high-quality randomized controlled clinical trials (RCTs) without any restriction on category. Methods: A systematic search of online database was performed from July 2010 to July 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 65 publications
8
49
0
Order By: Relevance
“…Others have reported on the association of the smoking status and the efficacy of nivolumab, a notion which can be supported biologically through the fact that the tumor mutational burden is higher in smokers [20]. However, in our data smoking history was not predictive for ICI efficacy, this may be due to low number of never smokers.…”
Section: Other Co-variatessupporting
confidence: 46%
“…Others have reported on the association of the smoking status and the efficacy of nivolumab, a notion which can be supported biologically through the fact that the tumor mutational burden is higher in smokers [20]. However, in our data smoking history was not predictive for ICI efficacy, this may be due to low number of never smokers.…”
Section: Other Co-variatessupporting
confidence: 46%
“…In a phase III randomized control trial with 1981 NSCLC patients, PD-1 inhibitors worked more efficaciously in patients with a smoking history while nonsmoking patients showed no survival benefit [ 121 ]. A similar meta-analysis in NSCLC, urothelial cancer and HNSCC showed that smokers benefited from anti PD-1/PD-L1 mono or combination therapy while nonsmokers benefitted from a combination of chemo- and immunotherapy [ 122 ]. One possible mechanism behind the increase in response to CPI treatment in smokers is related to an increase in PD-L1 expression by dendritic cells.…”
Section: Influence Of Lifestyle On Outcome Of Cpimentioning
confidence: 99%
“…For OS of chemoimmunotherapy compared to chemotherapy, both smokers and nonsmokers received a benefit with HRs of 0.72 (95% CI 0.61–0.85) and 0.45 (95% CI 0.28–0.71) respectively. 56 …”
Section: Smoking Historymentioning
confidence: 99%